Analyzing The Impact of Online Gaming Addiction on How Vocational Students Communicate - Faizza, Amalia Nur; Namira, Zahra Berlian; Wahyuni, Fitri; Rahayu, Ririn Ami (Universitas Negeri Malang, 2024)
The phenomenon of online gaming has gained worldwide popularity and attracted the attention of many people, especially the younger generation. However, the increasing fame of online games among teenagers has led to negative effects on social and personal areas. One of these areas is the way students communicate properly. This study aims to analyze the impact of online game addiction on students' interpersonal communication during school. This research uses a qualitative descriptive design with a case study approach. The subjects of this research are vocational students who have online game addiction and a counseling teacher. Data collection techniques used are observation and interview techniques. The instruments used are interview guidelines and observation guidelines. The data analysis technique used in the research is a fishbone diagram. The results of the research conducted found that online gaming addiction behavior affects the way students communicate on a daily basis. Students often swear, speak harshly, do not look at the other person, use a high tone of voice, and respond briefly when invited to communicate with peers.